Anatomical features of vegetative and reproductive organs of Savine juniper (Juniperus sabina L.) - Tserenkhand, Gundsambuu; Shinekhuu, Tumurjav (Mongolian Journal of Botany, 2023)
Savine juniper is a rare plant growing in the mountain-steppe belt of Mongolia, the upper part of which is harvested in large quantities of raw materials for traditional medicine and cosmetics, religious rituals, sterilization, and trade. For that reason, the range and resources of the species are reduced significantly. Currently, when the ecological balance is disturbed, the species has a weak ability to naturally regenerate. According, to this species must determine the results of anatomical structure and biochemical study of vegetative and reproductive organs for protection in nature, to ensure proper use and to standardize identifying raw materials. Therefore, we determined that it consists of the following main parts: cuticle, epidermis, palisade and spongy mesophyll tissue, excretory canal, and vascular bundle for determining the anatomical structure of needle-like leaf (needle). Anomocytic stomata are found only on the adaxial epidermis of the needle. However, the excretory canal is situated on the bottom side of the vascular bundle in the needle, it is characterized by being in between spongy tissue in the superficial triangle ledge section of the stem. Хонин арц (Juniperus sabina L.)–ны ургал болон үржлийн эрхтний анатомийн бүтцийн онцлог Хураангуй. Монгол орны уулын хээрийн бүслүүрт ургадаг ховор ургамал болох Хонин арц (Juniperus sabina L.)-ны газрын дээд хэсгийг уламжлалт эм болон гоо сайхны бүтээгдэхүүний түүхий эд, шашины ёс заншил, ариутгал, худалдаа найманы зорилгоор их хэмжээгээр түүж бэлтгэх болсонтой холбоотойгоор тухайн зүйлийн тархац хумигдан нөөц эрс багасч байна. Экологийн тэнцвэрт харьцаа алдагдаад байгаа өнөө үед тухайн зүйл нь байгалийн аясаар нөхөн сэргэх чадвар муутай учраас байгаль дээр нь хамгаалах, зөв зохистой хэрэглээг хангах, түүхий эдийг таньж тодорхойлох стандартыг боловсруулахад тухайн зүйлийн ургал болон үржлийн эрхтний анатомийн бүтэц, биохимийн судалгааны үр дүн зайлшгүй шаардлагатай. Тиймээс Хонин арцны шилмүүсний анатомийн бүтцийг тодорхойлоход кутикул, эпидерм, баганалаг эд, хөвсгөр паренхим, ялгаруулах суваг, дамжуулах багц гэсэн үндсэн хэсгүүдээс бүрддэг болохыг илрүүллээ. Аномоцит хэлбэрийн амсрууд шилмүүсний зөвхөн дээд гадаргууд байрлана. Харин ялгаруулах суваг нь шилмүүсэнд дамжуулах багцны долонгийн доод талд байрласан байхад, ишэнд гадаргуугийн сэртэн үүсгэсэн хэсэгт, үрийн хальсны зөөлөн эдийн дунд байрладаг онцлогтой. Түлхүүр үгс: Арц, эпидерм, паренхим, ялгаруулах суваг